Some perspectives on the application of artificial intelligence in encyclopedias - Mykola Zhelezniak; Oleksandr Ishchenko (Енциклопедичний Вісник України)
The article explores potential directions for employing generative artificial intelligence to enhance encyclopedia articles. Specifically, it proposes the idea of building additional knowledge-based content on encyclopedia platforms designed to summarize the information contained within articles (e.g., generating highlights, annotations, summaries, etc., through AI tools). According to the authors, such supplementary text blocks would be both interesting and beneficial for readers, aiming to improve article comprehension and retention of information while enabling them to quickly grasp the essence of extensive articles. A case study using selected articles from the Encyclopedia of Modern Ukraine demonstrates that virtual assistants like ChatGPT and Gemini exhibit a satisfactory level of proficiency in generating this type of supplementary content. However, the authors also emphasize the risks of editorial misuse of artificial intelligence, as it could be employed to generate primary content of articles replacing human authors. This raises concerns regarding the accuracy, reliability, and overall value of such content. Finally, the article underscores the need for scholarly discourse on ethical standards for the use of artificial intelligence by encyclopedia editorial officers.